Spatio-temporal propagation of Ca(2+) signals by cyclic ADP-ribose in 3T3 cells stimulated via purinergic P2Y receptors - Bruzzone, Santina (The Rockefeller University Press, 2003)
The role of cyclic ADP-ribose in the amplification of subcellular and global Ca(2+) signaling upon stimulation of P2Y purinergic receptors was studied in 3T3 fibroblasts. Either (1) 3T3 fibroblasts (CD38(−) cells), (2) 3T3 fibroblasts preloaded by incubation with extracellular cyclic ADP-ribose (cADPR), (3) 3T3 fibroblasts microinjected with ryanodine, or (4) 3T3 fibroblasts transfected to express the ADP-ribosyl cyclase CD38 (CD38(+) cells) were used. Both preincubation with cADPR and CD38 expression resulted in comparable intracellular amounts of cyclic ADP-ribose (42.3 ± 5.2 and 50.5 ± 8.0 pmol/mg protein). P2Y receptor stimulation of CD38(−) cells yielded a small increase of intracellular Ca(2+) concentration and a much higher Ca(2+) signal in CD38-transfected cells, in cADPR-preloaded cells, or in cells microinjected with ryanodine. Confocal Ca(2+) imaging revealed that stimulation of ryanodine receptors by cADPR or ryanodine amplified localized pacemaker Ca(2+) signals with properties resembling Ca(2+) quarks and triggered the propagation of such localized signals from the plasma membrane toward the internal environment, thereby initiating a global Ca(2+) wave.